Complete mitogenome of tea green leafhopper, Empoasca onukii (Hemiptera: Cicadellidae) from Anshun, Guizhou Province in China. Issue 2 (12th December 2017) - Liu, Jian-Hong; Sun, Cui-Ying; Long, Ju; Guo, Jian-Jun
Abstract: Tea green leafhopper, Empoasca onukii (Hemiptera: Cicadellidae), is one of the most serious pest insects in tea plantations in Asia. In this study, Mitogenome of this species was assembled with high coverage using Illumina sequencing data and the 15, 167 bp length was acquired. The base composition is 38.1% for A, 11.2% for C, 10.5% for G, and 40.2% for T. The mitogenome includes 13 protein-coding genes, 22 transfer RNA, and two ribosomal RNA genes. The phylogeny showed that it is closely related to E. vitis with high bootstrap value supported. The complete mitogenome of E. onukii can provide essential DNA molecular data for further phylogenetic and evolutionary analysis.